Cheeting in Mathematics Examinations - Omar Mejía Pérez (Universidad Autónoma de Baja California, 2014)
The exam is the most widely used assessment instrument in the history of education, primarily in mathematics. One of the main problems that happens in this resource, and make it an unreliable source to gather information, is plagiarism, copying or cheating. This issue occurs for many reasons, but has several consistencies in behavior of students when attending a test, as we could find in the experimental ethnographic exercises we did. We also noticed that although there is a direct relationship between the teacher's role as a supervisor of an examination and the level of plagiarism that occurs in it, the problem definitely has a greater connotation. Inside the classroom it can clearly see a culture of plagiarism which obstructs the educational process regarding ethical and educational justice is concerned.